Literature Review : Website sebagai Sarana Digital Marketing pada Sekolah Dasar dan Menengah di Era Cloud Computing - Sari, Nove Kurniati; Syaddam, Syaddam; Zulkarnain, Riski (Puslitbang Sinergis Asa Professional, 2025)
Websites and cloud computing are strategic foundations for supporting digital marketing, education management, and marketing strategies in primary and secondary education schools. The website functions as an official information centre that conveys the achievements that have been achieved by the school, activities, and superior programs, as well as a marketing tool to build school branding. Cloud computing technology supports efficient data management, collaboration, and marketing optimization. This study aims to review the role of websites and integration of productivity suite platforms in supporting digital marketing for education management in primary and secondary education schools, as well as the implementation of effective marketing strategies for non-profit schools. With strong branding, effective marketing communications, and data-driven analytics, schools can increase visibility, public trust, and audience engagement. The integration of technologies such as productivity suite platforms further strengthens the operational efficiency and effectiveness of school marketing. This study is expected to provide valuable insights for stakeholders in the field of education regarding best practices and innovative strategies in utilizing websites and cloud computing technology to achieve school goals in the digital era.